Hubungan Antara Status Gizi dan Stunting pada Usia 0-4 Tahun di Puskesmas Petir Kabupaten Serang Tahun 2023 - Adhika Afriadi; Dicky Santosa; Lisa Adhia Garina (Bandung Conference Series: Medical Science, 2024)
Abstract. Stunting is a disruption in children's growth and development that often occurs in the world until 2025, including Indonesia. The incidence of stunting is influenced by many factors, especially the nutritional status of children. The aim of this study was to analyze the relationship between nutritional status and stunting at ages 0–4 years. This research is an analytical observational study with a cross sectional approach. Research samples that met the research criteria were taken using purposive sampling totaling 269. Statistical analysis used SPSS version 29.0 with the bivariate Chi square test. Most of the stunted children were male, 153 children (56,9%), 173 children aged 0-24 months (66,5%), normal nutritional status 181 children (67,3%), and stunting stratification was short (stunting) 185 children (68,8%). There is a relationship between nutritional status and the incidence of stunting (p= 0,024). Nutritional status and stunting have a significant relationship, with the largest distribution of both stunted and severely stunted occurring in the normal nutrition group and more frequently occurring in men compared to women. Monitoring body weight and length or height is important to do regularly to detect malnutrition and risk of stunting. Abstrak. Stunting menjadi gangguan tumbuh kembang anak yang banyak terjadi didunia hingga tahun 2025, termasuk Indonesia. Kejadian stunting dipengaruhi oleh banyak faktor terutama adalah status gizi pada anak. Tujuan penelitian ini untuk menganalisis hubungan antara status gizi dengan stunting pada usia 0–4 tahun. Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross sectional. Sampel penelitian yang memenuhi kriteria penelitian diambil menggunakan purposive sampling berjumlah 269. Analisis statistik menggunakan SPSS versi 29.0 dengan uji bivariat Chi square. Sebagian besar anak stunting berjenis kelamin laki-laki sebanyak 153 anak (56,9%), usia 0-24 bulan 173 anak (66,5%), status gizi normal 181 anak (67,3%), dan stratifikasi stunting adalah pendek ( stunting) 185 anak (68,8%). Terdapat hubungan antara status gizi dengan kejadian stunting (p = 0,024). Status gizi dan stunting mempunyai hubungan yang signifikan, dengan distribusi terbesar baik stunting maupun stunting berat terjadi pada kelompok gizi normal dan banyak terjadi pada jenis kelamin laki-laki dibandingkan dengan perempuan. Pemantauan berat badan dan panjang atau tinggi badan penting dilakukan secara rutin untuk mendeteksi malnutrisi dan risiko stunting.